Analisis Penentuan Harga Pokok Penjualan pada UMKM Tahu Bakso Miwiti - Azrina Amalia, Valya; Ausyaf Diefa Hanifah, Atsil; Salsabila Ilena Suhara, Alysa; Astuti Tri Tartiani, Yuni (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2024)
The background of this research is the importance of accurate and systematic COGS calculations for MSMEs in setting competitive and profitable selling prices. This study aims to analyze in depth the process of determining the cost of goods sold (COGS) in determining the selling price of products at Tahu Bakso Miwiti UMKM. The research method used is a qualitative approach with descriptive analysis. Data were collected through in-depth interviews with business owners and collection of relevant documents. The results showed that Tahu Bakso Miwiti MSMEs do not yet have a structured and systematic COGS calculation system. Most of the selling price decisions taken so far are based on consumer perceptions and the target profit margin set, without considering all production costs in detail and thoroughly. This study concludes that the application of the full costing method in the calculation of COGS will provide a stronger and more valid basis for MSMEs to determine a more appropriate selling price. Therefore, it is recommended that MSMEs implement a more comprehensive COGS calculation to increase profitability and business competitiveness in an increasingly competitive market.